Pengaruh Putih Telur Dan Ikan Gabus Terhadap Penyembuhan Luka Perineum Pada Ibu Nifas Di Wilayah Kerja Puskesmas Tekaga Dewa Kota Bengkulu - Fitrinisa, Aulia (JURNAL BESUREK JIDAN, 2024)
According to the World Health Organization (WHO) in 2023, the maternal mortality rate will reach 189 per 100 thousand live births. One cause is infection of the perineal wound which is not treated during the postpartum period. This research aims to see the effect of egg white and snakehead fish on perineal wound healing on postpartum women in the Telaga Community Health Center Working Area, Bengkulu City in 2024. This research uses a quasi-experimental design method with a post test only research design with two group design. The population of this study was post partum mothers in the Telaga Dewa Community Health Center Working Area, Bengkulu City, the sampling technique used accidental sampling with a total sample of 46 post partum mothers. Data were analyzed using univariate and bivariate analysis using the Independent T Test if the data distribution was normal or the Man Whitney Test if the distribution was not normal. The results of the research showed that there was an effect between giving egg white and snakehead fish on perineal wound healing with a P value = 0.046 with an average value of wound healing in the intervention group with egg white of 6.06, while giving the control group with snakehead fish obtained an average of 5. .58 so it can be seen that the control group given snakehead fish healed wounds relatively faster than the intervention group given egg white. It is hoped that the results of this research can provide education to pregnant women about the importance of caring for perineal wounds after giving birth, which can prevent infection in the wound.